Field Visit to Karnal in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In February of this year, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) South Asia program ventured out to visit farmers in Karnal, India, to learn more about their practices and activities. These pictures showcase what we encountered during this field visit - farmers working hard in the fields. Photo: N. Sigtia (CCAFS SA)